2019
DOI: 10.13189/ujer.2019.070409
|View full text |Cite
|
Sign up to set email alerts
|

Learning Vocabulary through Collocating on Quizlet

Abstract: The difficulty in learning vocabulary is a problem that lies in not anchoring the new items to relevant established entities in cognitive structure. Different categories of associations have been reported to aid facilitating vocabulary acquisition. Collocating vocabulary items is a type of association that is considered to be more efficient in retrieval. The present study sought to investigate whether collocating the lexical items on Quizlet can facilitate acquisition of the vocabulary items, and whether it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Several previous studies concluded that the primary function of Quizlet helped to deve-lop language intelligence, especially in increasing vocabulary (Andarab, 2019;Anjaniputra & Salsabila, 2018;Dizon, 2016;Tri, 2015;Wahjuningsih, 2018;Wright, 2016)and whether it is likely to be more effective than learning decontextualized individual words. In so doing, 70 upper-intermediate English as a foreign language (EFL.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies concluded that the primary function of Quizlet helped to deve-lop language intelligence, especially in increasing vocabulary (Andarab, 2019;Anjaniputra & Salsabila, 2018;Dizon, 2016;Tri, 2015;Wahjuningsih, 2018;Wright, 2016)and whether it is likely to be more effective than learning decontextualized individual words. In so doing, 70 upper-intermediate English as a foreign language (EFL.…”
Section: Introductionmentioning
confidence: 99%
“… Chaikovska and Zbaravska (2020) also state that associating unknown words with visuals, such as bright graphics and exaggerated pictures, benefits vocabulary acquisition. According to Andarab (2019) , using technology to contextualize vocabulary items during vocabulary acquisition improves the vocabulary learning process. This reinforcement of learning through visual aids and contextualization aligns with cognitive theories of multimedia learning, which posit that learners can more effectively process and retain information when it is presented in both verbal and visual formats.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with the research by Körlü and Mede (2018) , which indicated that Quizlet had a positive impact on students’ performance and autonomy in vocabulary learning ( Körlü and Mede, 2018 ). Also, several studies have demonstrated the positive influence of Quizlet on student’s cognitive learning such as vocabulary learning and retention ( Barr, 2016 ; Özer and Koçoğlu, 2017 ; Ashcroft et al, 2018 ; Körlü and Mede, 2018 ; Sanosi, 2018 ; Andarab, 2019 ; Çinar and Ari, 2019 ; Toy, 2019 ; Arslan, 2020 ; Chaikovska and Zbaravska, 2020 ; Tanjung, 2020 ; Van et al, 2020 ; Akhshik, 2021 ; Aksel, 2021 ; Fursenko et al, 2021 ; Ho and Kawaguchi, 2021 ; Kurtoğlu, 2021 ; Setiawan and Putro, 2021 ; Atalan, 2022 ; Lin and Chen, 2022 ; Nguyen and Van Le, 2022 , 2023 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Instead, it needs the user to input the vocabulary and meaning of the word into the Quizlet system itself. This method makes it very inconvenient when many words need to be entered [18].…”
Section: Related Workmentioning
confidence: 99%